The kinematic factors of physical motions during air pistol shooting - Kim, M.-S. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to analyze the kinematic factors of motion during air pistol shooting. Method: This study aimed to investigate changes in forces during movement and determine the factors that affect changes in force during the first, middle, and last periods of shooting an air pistol. Two ground reaction force systems (force platform), SCATT (a shooting training system), and EMG (electromyogram) to measure the action potentials in the muscles of the upper body were used in this study. Four university air pistol players (age: 19.75 years, height: 175.50 cm, body mass: 69.55±11.50 kg, career length: 6.25±6 years) who are training to progress to a higher rank were enrolled. Results: In terms of the actual shooting results, the mean score in the middle section was 42.48±1.74 points, higher than those in the first and the last periods when using SCATT. The gunpoint moved 13.48 mm more vertically than horizontally in the target trajectory. With respect to action potentials of muscles measured using EMG, the highest action potentials during the aiming-shooting segments, in order higher to lower, were seen in the trapezius (intermediate region), trapezius (superior region), deltoid (lateral), and triceps brachii (long head). The action potentials of biceps brachii and brachioradialis turned out to be high during grasping motion, which is a preparatory stage. During the final segment, muscle fatigue appeared in the deltoid (lateral), biceps brachii (long head), brachioradialis, and trapezius (intermediate region). In terms of the ground reaction force, during the first period of shooting, there was a major change in the overall direction (left-right Fx, forward-backward Fy, vertical Fz) of the center of the mass. Conclusion: The development and application of a training program focusing on muscle groups with higher muscle fatigue is required for players to progress to a higher rank. Furthermore, players can improve their records in the first period if they take part in a game after warming up sufficiently before shooting in order to heighten muscle action potentials, and are expected to maintain a consistent shooting motion continuously by restoring psychological stability.